3-10z=3(2z-6)

Simple and best practice solution for 3-10z=3(2z-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-10z=3(2z-6) equation:


Simplifying
3 + -10z = 3(2z + -6)

Reorder the terms:
3 + -10z = 3(-6 + 2z)
3 + -10z = (-6 * 3 + 2z * 3)
3 + -10z = (-18 + 6z)

Solving
3 + -10z = -18 + 6z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6z' to each side of the equation.
3 + -10z + -6z = -18 + 6z + -6z

Combine like terms: -10z + -6z = -16z
3 + -16z = -18 + 6z + -6z

Combine like terms: 6z + -6z = 0
3 + -16z = -18 + 0
3 + -16z = -18

Add '-3' to each side of the equation.
3 + -3 + -16z = -18 + -3

Combine like terms: 3 + -3 = 0
0 + -16z = -18 + -3
-16z = -18 + -3

Combine like terms: -18 + -3 = -21
-16z = -21

Divide each side by '-16'.
z = 1.3125

Simplifying
z = 1.3125

See similar equations:

| 7x-17y=17.83 | | 5m+2+8m=2m+1 | | 7(4)-4(2)=-5 | | 7(-3)-4(-4)=-5 | | 13x-5[2x-(x+1)]=15-2[3x-5(x+3)] | | 3/27+48/54= | | 7(1)-4(3)=-5 | | 2x-5=-x^2 | | -34=4(3)+7 | | 14y-11x=14.701 | | -5=4(-3)+7 | | 5=-6(3+5q)-9q | | 4x^2+3=9x | | 5/8+6/16= | | 23=4(4)+7 | | 13=4(5)+7 | | 7a+4(a-9)=6a+4 | | 6/10+10+25= | | 6x-4x=12 | | -5(-5v+7)-4v=5(v-4)-9 | | 6x-28= | | 2(1)+9(2)=12 | | 9/4+6/8= | | 6.5+8y=32 | | 25x+75x= | | 2(-7)+9(3)=13 | | 495=2x-(1-9x)+1 | | 2(4)-5(2)=11 | | 8x^2+12x+18=0 | | 3x+32= | | 2(-7)-5(-5)=11 | | 5x-11=-29 |

Equations solver categories